2004
DOI: 10.1590/s1415-790x2004000400002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for esophageal cancer in non-smokers and non-drinkers: a case-control study in Uruguay

Abstract: In order to analyze possible associations of lifestyle factors with esophageal cancer among non-smokers and non-drinkers, the authors carried out the present study. Special emphasis was placed on the analysis of "mate" (infusion of the herb Ilex paraguariensis) drinking, which has been associated with most cancers of the upper aerodigestive tract. The study was conducted at the Instituto Nacional de Oncología in Montevideo, Uruguay. Data corresponded to 73 esophageal cancer cases and 219 controls. A detailed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(8 reference statements)
2
4
0
1
Order By: Relevance
“…This pattern is associated with a low educational level, rural residence out of the capital city, and having a birthplace located mainly at northern counties as it is shown in Table 3. Moreover, these facts were already described in a previous study on esophageal cancer in nondrinkers and nonsmokers (47). Concerning the drinker pattern, high loadings of barbecued fried meat, processed meat, and fried eggs suggest similarities with the Western pattern extracted by the Swedish authors (26).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This pattern is associated with a low educational level, rural residence out of the capital city, and having a birthplace located mainly at northern counties as it is shown in Table 3. Moreover, these facts were already described in a previous study on esophageal cancer in nondrinkers and nonsmokers (47). Concerning the drinker pattern, high loadings of barbecued fried meat, processed meat, and fried eggs suggest similarities with the Western pattern extracted by the Swedish authors (26).…”
Section: Discussionsupporting
confidence: 70%
“…This appears to be somewhat paradoxical. A previous study on lung cancer among never smokers reported the protective effect of cheese (47). In our study, this food item loads highly in the high-fat pattern.…”
Section: Discussionsupporting
confidence: 50%
“…Of the series of studies conducted in Uruguay (5,7,(9)(10)(11), it is interesting to single out the one based on data of esophagus cancer patients who were not smokers or consumers of alcohol, thus excluding the two most important confounding factors: tobacco and alcohol consumption (11). The authors described a model where daily consumption (OR 2.20, 95%CI: 1.02-4.91, for 1 L or more Uruguay, Montevideo (1993)(1994)(1995) Brazil, Campinas (1991)(1992)(1993)(1994)(1995) Cuba, Villa Clara (1995)(1996)(1997) Argentina, Bahia Blanca (1993)(1994)(1995)(1996)(1997) Costa Rica (1995Rica ( -1996 Ecuador, Quito (1993)(1994)(1995)(1996)(1997) 0.0 0.5 1.0 1.5 2.0 2.5 3.0 3.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…The need for additional studies on a greater number of healthy individuals to validate these findings was suggested, but no such further studies have been published to date. In Argentina, a hospital-based casecontrol study was conducted by Castelletto et al (8), using a design similar to those used in Uruguay and Brazil (6,7,11). This study found an increased risk associated with tobacco and alcohol consumption, but not with mate drinking in general.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…local studies about 'mate' (a hot infusion made from the herb ilex paraguariensis, which is a staple nonalcoholic beverage in temperate South America) and its role on cancer were mainly focused on the upper aerodigestive sites (Vassallo et al, 1985;De Stefani et al, 1988;1990;Castellague et al, 2000;Sewram et al, 2003;Ronco et al, 2004;Deneo-Pellegrini et al, 2013;Lubin et al, 2014), usually showing positive associations with these tumors.…”
mentioning
confidence: 99%